Juegos de simulación por ordenador : un útil para la enseñanza a todos los niveles - Barberà, O.; Sanjosé López, V. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
This paper enhances some of the great number of science educational applications of computers simulation games, and briefly discusses the relationship with the physical structure of computers and living world.